Multiple Sclerosis and Oligodendroglioma: An Exceptional Association. (7th August 2014) - Carvalho, Ana Teresa; Linhares, Paulo; Castro, Lígia; Sá, Maria José
Abstract : The cooccurrence of multiple sclerosis (MS) and oligodendroglioma is very rare. We present a 43-year-old male patient with the diagnosis of MS lasting for 14 years who developed seizures and right hemiparesis; cerebral MRI revealed an already known extensive lesion, previously misdiagnosed as tumefactive demyelinating lesion. Cerebral biopsy leads to oligodendroglioma diagnosis, successfully treated with radiotherapy. The diagnosis of a brain tumor in a MS patient is challenging. The atypical clinical and radiological features are the key for accurate diagnosis. In such cases, a brain tumor has to be kept in mind no matter how rare this association is.